Note. Quality evaluation of cupuaçu (Theobroma grandiflorum) purée after pasteurization and during storage - Silva, F.M. (2011)
Cupuaçu (Theobroma grandiflorum ) is an Amazonian fruit with a pleasant aroma and flavor, which offers a great economic potential. Purée of cupuaçu pulp was pasteurized (70 and 90 °C), and stored for half a year at 18 and 38 °C. The pasteurization was effective in microbial and enzyme inactivation, and stabilization of the purée. Peroxidase enzyme was inactivated (polyphenoloxidase was not de tected in raw cupuaçu), some cupuaçu 'fresh notes' were lost, and the color changed slightly during pasteurization at both temperatures. Since, except for color, no significant quality differences were detected between samples processed at 70 °C and 90 °C, the pasteurization at 90 °C is recommended. The parameters that changed most during storage were the color, flavor, aroma and sugars. The purée got darker, especially at 38 °C, and the non-reducing sugars were converted into reducing sugars, while the total sugars remained constant. The final quality was determined by the storage tempera ture and not by the pasteurization temperature. The total color difference, TCD*, was well modeled by first-order reversible kinetics.